Peran Hospitalitas Kristen Terhadap Penyandang Disabilitas (Retardasi Mental) - Filia Amelia Kasinda (MAGENANG : Jurnal Teologi dan Pendidikan Kristen, 2022)
The standard of acceptance in society is one's normality. But people with disabilities are stigmatised as marginalized people and vulnerable to violence and discrimination. Such situations reflect the great danger that threatens people with intellectual disabilities (Mental Retardation). Their mental state is considered a punishment for sin and labeled as abnormal. This paper aims to formulate the role of Christian hospitality for people with disabilities (Mental retardation). This research uses qualitative approach with theological research type and social descriptive research. The result of this study is, first Christian hospitality should be one of the pioneers of hospitalization for people with disabilities (mental retardation). Second, disability must be addressed and understood from the concept of imago dei that man is created as a picture and similar to God.